Synthesis of pyrrol-pyridazyl-triazolyl-pyridines via Cu(I)-catalyzed azide-alkyne 1, 3-dipolar cycloaddition reaction. Issue 13 (2nd July 2016) - Yang, Wu; Fu, Leixia; Wu, Jie; Song, Chuanjun
ABSTRACT: Conjugated alternative donor–acceptor type pyrrol-pyridazyl-triazolyl-pyridine N -heterocyclic systems were synthesized via Cu(I)-catalyzed azide-alkyne 1, 3-dipolar cycloaddition reaction of pyrrol-pyridazylacetylene with azidopyridines. GRAPHICAL ABSTRACT: